Seeds of sustainablility : lessons from the birthplace of the Green Revolution - Matson, P. A. (Pamela A.) (Washington, DC : Island Press, 2012)
Seeds of Sustainability is a groundbreaking analysis of agricultural development and transitions toward more sustainable management in one region. An invaluable resource for researchers, policymakers, and students alike, it examines new approaches to make agricultural landscapes healthier for both the environment and people. The Yaqui Valley is the birthplace of the Green Revolution and one of the most intensive agricultural regions of the world, using irrigation, fertilizers, and other technologies to produce some of the highest yields of wheat anywhere. It also faces resource limitations, threats to human health, and rapidly changing economic conditions. In short, the Yaqui Valley represents the challenge of modern agriculture: how to maintain livelihoods and increase food production while protecting the environment. Renowned scientist Pamela Matson and colleagues from leading institutions in the U.S. and Mexico spent fifteen years in the Yaqui Valley in Sonora, Mexico addressing this challenge. Seeds of Sustainability represents the culmination of their research, providing unparalleled information about the causes and consequences of current agricultural methods. Even more importantly, it shows how knowledge can translate into better practices, not just in the Yaqui Valley, but throughout the world.
Why the Yaqui Valley? An introduction / Pamela Matson and Walter Falcon -- A brief history of the Yaqui Valley / Ashley Dean -- Looking for "win-wins" in intensive agriculture / Pamela Matson, Rosamond Naylor, and Ivan Ortiz-Monasterio -- Ecosystems and land use change in the Yaqui Valley: does agricultural intensification "spare land for nature"? / Pamela Matson and Peter Jewett -- Linking knowledge with action for sustainable development: A case study of change and effectiveness / Ellen McCullough and Pamela Matson -- Exploring vulnerability in the Yaqui Valley human-environment system / Pamela Matson, Amy Luers, and Ellen McCullough -- From wheat to waves and back again: connections between the Yaqui Valley and the Gulf of California / Michael Beman and Amy Luers -- The Yaqui Valley's agricultural transition to a more open economy / Rosamond Naylor and Walter Falcon -- Agricultural research and management at the field scale / Ivan Ortiz-Monasterio and David Lobell -- Nitrogen in the Yaqui Valley: sources, transfers, and consequences / Toby Ahrens [and others] -- Water resources management in the Yaqui Valley / Gerrit Schoups [and others] -- Lessons learned / Pamela Matson, Rosamond Naylor, and Ivan Ortiz-Monasterio.
Includes bibliographical references (pages 259-277) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Sustainable agriculture -- Mexico -- Yaqui River Valley -- Case studies; Sustainability -- Mexico -- Yaqui River Valley -- Case studies; Green Revolution -- Mexico -- Yaqui River Valley -- Case studies; Agriculture durable -- Mexique -- Yaqui, Vallée du -- Études de cas; Durabilité de l'environnement -- Mexique -- Yaqui, Vallée du -- Études de cas; Révolution verte -- Mexique -- Yaqui, Vallée du -- Études de cas; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture; Green Revolution; Sustainability; Sustainable agriculture; Mexico -- Yaqui River Valley; afvalwaterbehandeling; waste water treatment; waterbeheer; water management; landbouw; agriculture; duurzame ontwikkeling; sustainable development; geschiedenis; history; ecosystemen; ecosystems; milieu; environment; Environmental Sciences (General); Milieuwetenschappen (algemeen); Case studies; Case studies; Études de cas